Efektifitas Modifikasi Perilaku Teknik Assertive Training untuk Meningkatkan Kepercayaan Diri Remaja Korban Bullying - Marlinda, Cut Nayya; Setyaningsih, Endang (Jejak digital: Jurnal Ilmiah Multidisiplin, 2026)
This study aims to examine the effectiveness of behavior modification using assertive training techniques to increase the self-confidence of adolescent victims of bullying in Banda Aceh. Utilizing a quasi-experimental design with a Non-equivalent Control Group Design, this study involved 40 eighth-grade students selected through purposive sampling from two public junior high schools. The subjects were divided into an experimental group (n = 20) which received eight sessions of assertive training, and a control group (n = 20). Data were collected using the Self-Confidence Scale (Cronbach’s Alpha = 0.885) and analyzed using the Independent Sample T-Test via SPSS 26. The descriptive analysis showed a substantial increase in the experimental group’s mean score from 52.45 to 79.15, whereas the control group only changed from 53.10 to 54.65. The t-test on gain scores revealed a highly significant difference between the two groups (t = 8.432, p = 0.000 < 0.05). These results demonstrate that assertive training effectively restructures verbal and non-verbal responses, decreases social anxiety, and enhances the self-efficacy of bullying victims. School counselors are highly recommended to integrate this module into group counseling services.